A Novel Berberine–Glycyrrhizic Acid Complex Formulation Enhanced the Prevention Effect to Doxorubicin-Induced Cardiotoxicity by Pharmacokinetic Modulation of Berberine in Rats - Zhang, Shichang; Zhao, Yiwei; Tan, Liangjun; Wu, Sheng; Zhang, Qing; Zhao, Boxin; Li, Guofeng (Frontiers in Pharmacology, 2022)
Developing a new drug delivery system is one of the useful approaches to overcome the limited use of berberine (BBR) to enhance absorption and bioavailability. We prepared a novel berberine-glycyrrhizic acid complex formulation (BBR-GL complex) to increase the plasma concentration and bioavailability of BBR by improvement of BBR solubility and lowering absorption barrier. The complex formulation with ratios of BBR and GL of 1:1 was developed through the self-assembly process and evaluated in vitro. Compared with BBR and BBR/GL physical mixture, the BBR-GL complex showed different characteristics by SEM, DSC, FT-IR, PXRD measurement. In pharmacokinetic evaluation, BBR-GL complex significantly increased the plasma concentration of BBR and the major metabolite berberburine (BBB) with the AUC of BBR elevated 4.43 folds, while the complex was safe as BBR. Furthermore, doxorubicin(DOX) was used to induce cardiotoxicity. Hematological study, histopathological examinations, electrocardiography (ECG), cardiac secretion measurement and biochemical index analysis proved that the model of doxorubicin-induced cardiotoxicity (DIC) was conducted successfully. With the AUC of BBR increasing in BBR-GL complex and the absorbed complex itself, BBR-GL complex enhanced prevention effect to DIC, exhibited significant prevention effect to attenuate heart damage. Our findings demonstrated that a novel BBR-loaded BBR-GL complex formulation could increase BBR plasma concentration. Improvement of BBR bioavailability by BBR-GL complex could coordinate with GL to attenuate DOX-induced cardiotoxicity. With the safety of the drug delivery system is concerned at present, BBR-GL complex could be a potential therapeutic formulation for the prevention of cardiac damage in doxorubicin clinical application.